GM-CSF induces noninflammatory proliferation of microglia and disturbs electrical neuronal network rhythms in situ - Dikmen, Hasan Onur; Hemmerich, Marc; Lewen, Andrea; Hollnagel, Jan-Oliver; Chausse de Freitas, Bruno; Kann, Oliver (Journal of neuroinflammation, 2020)
The granulocyte-macrophage colony-stimulating factor (GM-CSF) (or CSF-2) is involved in myeloid cell growth and differentiation, and, possibly, a major mediator of inflammation in body tissues. The role of GM-CSF in the activation of microglia (CNS resident macrophages) and the consequent impacts on neuronal survival, excitability, and synaptic transmission are widely unknown, however. Here, we focused on electrical neuronal network rhythms in the gamma frequency band (30-70 Hz). Gamma oscillations are fundamental to higher brain functions, such as perception, attention, and memory, and they are exquisitely sensitive to metabolic and oxidative stress.
Published: 11 August 2020
Gesehen am 18.09.2020